2020
DOI: 10.1002/jmri.27251
|View full text |Cite
|
Sign up to set email alerts
|

Benign Neoplasms, Mass‐Like Infections, and Pseudotumors That Mimic Hepatic Malignancy at MRI

Abstract: A variety of conditions may mimic hepatic malignancy at MRI. These include benign hepatic tumors and tumor‐like entities such as focal nodular hyperplasia‐like lesions, hepatocellular adenoma, hepatic infections, inflammatory pseudotumor, vascular entities, and in the cirrhotic liver, confluent fibrosis, and hypertrophic pseudomass. These conditions demonstrate MRI features that overlap with hepatic malignancy, and can be challenging for radiologists to diagnose accurately. In this review we discuss the MRI ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…Imaging features on MRI supportive of an adenoma in patients with no risk factors for liver disease are an arterial phase enhancing hepatic mass with variable signal intensity on later phase images or hypo‐intensity on hepatobiliary phase. In addition, the lesion may have the following associated features: intra‐lesional steatosis, increased signal intensity of T2 weighted or diffusion‐weighted images, presence of blood products, and no associated central scar 13‐15 . Of the 167 patients that met selection criteria, demographic data such as age, ethnicity, and gender were collected.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Imaging features on MRI supportive of an adenoma in patients with no risk factors for liver disease are an arterial phase enhancing hepatic mass with variable signal intensity on later phase images or hypo‐intensity on hepatobiliary phase. In addition, the lesion may have the following associated features: intra‐lesional steatosis, increased signal intensity of T2 weighted or diffusion‐weighted images, presence of blood products, and no associated central scar 13‐15 . Of the 167 patients that met selection criteria, demographic data such as age, ethnicity, and gender were collected.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the lesion may have the following associated features: intra-lesional steatosis, increased signal intensity of T2 weighted or diffusion-weighted images, presence of blood products, and no associated central scar. [13][14][15] Of the 167 patients that met selection criteria, demographic data such as age, ethnicity, and gender were collected. Clinical data collected included: history of Type II diabetes, body mass index (BMI), tobacco and alcohol use (yes or no), oral contraception (OCP) use, duration and type used if available, anabolic steroid use, date of initial imaging, and date of most recent follow-up MRI scan.…”
Section: Patientsmentioning
confidence: 99%
“…Biopsy is generally avoided, given the vascular nature of hemangiomas, although reports have indicated that risk of bleeding with biopsy of hemangiomas is low (0.15%) if small needles are used (142). Once the diagnosis of hemangioma is confirmed, no further follow-up imaging is needed, except for patients with underlying cirrhosis or risk of HCC, because lesions can mimic hemangioma early in the course of malignancy development (143,144). These patients should undergo follow-up imaging as recommended for FLL in the AASLD Hepatocellular Carcinoma Guidance (145).…”
Section: Hemangiomamentioning
confidence: 99%